2010
DOI: 10.1016/j.jjcc.2009.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Bare metal stent implantation for in-stent restenosis with a drug-eluting stent

Abstract: Following the positioning of a bare metal stent (BMS) implant, a yellow plaque is healed with a reduction of the color grade and thrombogenicity, i.e. vulnerability by angioscopy in the chronic phase ("plaque sealing" of BMS; the "whitening effect" of BMS). However, we have reported that thrombus and yellow plaque increases at the drug-eluting stent (DES) site. A 71-year-old man underwent percutaneous coronary intervention using two DESs for a severe stenotic lesion in his right coronary artery. Follow-up coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The hyperglycemic state itself is of crucial importance for the excessive risk of diabetic patients with an enhanced thrombotic milieu or endothelial dysfunction by increasing oxidative stress [32]. DES has a greater beneficial effect compared to a bare metal stent or balloon angioplasty [2,5,33] in terms of reducing clinical events in patients with DM, but DES could not show such a beneficial effect comparing patients with and without DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperglycemic state itself is of crucial importance for the excessive risk of diabetic patients with an enhanced thrombotic milieu or endothelial dysfunction by increasing oxidative stress [32]. DES has a greater beneficial effect compared to a bare metal stent or balloon angioplasty [2,5,33] in terms of reducing clinical events in patients with DM, but DES could not show such a beneficial effect comparing patients with and without DM.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous coronary intervention (PCI) in patients with diabetes mellitus (DM) is associated with an increased risk of adverse clinical outcomes compared with those without DM [1][2][3]. Recent data have demonstrated that drug-eluting stents (DES) reduce the incidence of restenosis and the need for repeated revascularization compared with bare-metal stents in patients with DM [4,5]. Furthermore, sirolimus-eluting stents [6] (SES) and paclitaxel-eluting stents [7] (PES) dramatically reduce angiographic measures and clinical events compared with bare metal stents in patients with and without DM.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of DES, the rates of restenosis and target-vessel revascularization have dropped below 10%. However, angioscopy showed that the restenosis site in patients treated with DES looked like vulnerable plaque [22]. Therefore, statins could still be useful after PCI even in patients treated with DES.…”
Section: Discussionmentioning
confidence: 99%
“…Thick, white neointima covered the ISR lesion, without restenosis being observed at the follow-up examination. 20) This case suggests that angioscopic observation directly impacts the choice of an effective therapy.…”
Section: Isr After Des Implantationmentioning
confidence: 98%